Dungun County Golf Club - Towards Business Orientation / Ahmad Othman, Wan Ibrahim Wan Ismail and Ghazali Hj Awang - Othman, Ahmad; Wan Ismail, Wan Ibrahim; Awang, Ghazali (2005)
The objective of this report is to study and identify the current problems of a selected company namely “Dungun Country Golf Club (DCGC)” which is located in Dungun, Terengganu. This club was officially registered somewhere in late 1960s as Dungun Golf Club under the society Act 1966 and was re-registered under a different name in 1983 as Dungun Country Golf Club. DCGC was established to provide sports and recreational services to its members which were previously comprised of mostly Government servants. Currently, the memberships of the club were also open to non-government servants but with different rate of registration fees. The facilities currently available at DCGC are only 18 holes golf course, golf driving range and a swimming pool. The current numbers of registered members are about 250 inclusive of all categories of membership. The club are currently managed by a group of personnel appointed by the members whose act as “The Management Committee ” and the daily operations of the club are run by a Club Manager (currently vacant) with the assistance of eleven employees of various categories.